Identification of Competing Endogenous RNA and Micro-RNA Profiles and Regulatory Networks in 4-Nonylphenol-induced Impairment of Sertoli Cells - Liu, Wenjie; Wang, Zhaokai; Hu, Xiaopeng (Frontiers in Pharmacology, 2021)
The xenoestrogens nonylphenols (NPs), which are materials used in the plastic polymer industry, are considered endocrine disruptors in a wide range of organisms. Studies have shown that human health problems, such as infertility and reproductive toxicology, are linked with NPs. However, the mechanism by which NPs interfere with male reproduction is not fully elucidated. Here, we found that 4-NP can result in male reproductive impairment and reduce androgen receptor (AR) protein levels in rat sertoli cells in vitro and in vivo. Moreover, we performed RNA sequencing to assess the differential expression of ceRNAs in rat sertoli cells treated with 4-NP. Bioinformatics methods, such as Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) database and ceRNA functional network analyses, were used to investigate the sequencing data and gain further understanding of the biological processes. Our analysis revealed a core set of mRNAs (Ar, Atf6 and Cbp), and circRNAs (circ673, circ1377, circ1789, and circPTEN) that were selected and validated by RT-qPCR. In addition, the head-to-tail splicing of circ673, circ1377, circ1789, and circPTEN was identified by Sanger sequencing. These findings provide the first insight into the ceRNA expression profiles of rat sertoli cells and reveal that ceRNAs participate in 4-NP-induced impairment of sertoli cell function, thereby indicating potential therapies for both reproductive toxicology and male infertility.